(untitled) (KASBIT Business Journal, 2025)
The rapid proliferation of digital media has altered consumer behavior, particularly among young individuals who are influenced by social dynamics present in online spaces. This research investigates the contrasting impact of Fear of Missing Out (FOMO) and Joy of Missing Out (JOMO) on online consumption of this demographic. As both concepts are related to social experiences, a moderating effect of social comparison provides a comprehensive insight into the comparison of their impacts. FOMO, characterized by anxiety over missing valued experiences and social engagement, often drives impulsive buying behaviors. In contrast, JOMO reflects a conscious decision to opt out of such experiences, promoting mindfulness in consumption choices. This study investigates these concepts by gathering data through a structured questionnaire administered to 595 university students, which was further analyzed through SEM in SmartPLS software. The study delineates the extent to which FOMO fosters impulsive buying tendencies while JOMO mitigates these inclinations through social comparison. The findings reveal empirical insights into how these competing psychological forces influence online consumption among university students, allowing marketers to understand and navigate the delicate balance between leveraging FOMO-driven urgency and fostering JOMO-induced contentment in their marketing strategies. Ultimately, this research contributes to the understanding of contemporary consumer psychology and its implications for digital marketing practices.